Endoscopic intermuscular dissection for management of 10- to 20-mm rectal neuroendocrine tumors: Pilot study (with video) - Huang, Silin; Li, Bo; Deng, Huizhao; Yang, Guang; Zhang, Ronggang; Ren, Jianzhen; Liu, Nan; Liao, Suhuan (Endoscopy International Open, 2025)
Endoscopic intermuscular dissection (EID) is associated with higher rates of negative margins in treating rectal neuroendocrine tumors (R-NETs), as reported in case studies. However, evidence regarding the safety and effectiveness of EID remains insufficient. This study aimed to evaluate clinical safety and effectiveness of EID in treating 10- to 20-mm R-NETs.Retrospective clinical data from patients with 10- to 20-mm R-NETs who had undergone EID from 2019 to 2024 were collected from a tertiary hospital. The primary outcome was the histological complete resection rate and secondary outcomes included en bloc resection rate and technical success rate.Twelve patients who had undergone EID were included, with one patient excluded for pathology indicative of a leiomyoma. Among the 11 patients (mean age, 42.45 years; 72.73% males), median diameter was 11.55 mm (interquartile range 10–13 mm). All patients underwent en bloc resection and postoperative pathology confirmed negative horizontal and vertical margins, achieving a histological complete resection rate of 100%. Mean procedure time was 58.55 minutes (standard deviation [SD] 13.66 minutes) and mean postoperative hospital stay was 5.7 days (SD 1.00). One patient developed fever and another experienced abdominal pain, both of which resolved within 24 hours. There were no cases of bleeding or perforation intraoperatively or postoperatively. During a mean follow-up of 31.73 months, there were no residual tumors, local recurrences, or metastases.EID is a promising treatment for 10- to 20-mm R-NETs, with high initial cure rates, and a new option for endoscopic resection. More studies of the procedure are needed.
Keywords: Endoscopy Lower GI Tract; Endoscopic resection (polypectomy, ESD, EMRc, ...); Tissue diagnosis; Polyps / adenomas / ...